Estudio demográfico de la población canina y felina y su incidencia en el desarrollo urbano de la Ciudad de Guaranda - Guerra Maiguashca, Andrea Roxana (2017)
In the Province of Bolívar, Guaranda city, urban parishes Ángel Polibio Chávez, Gabriel Ignacio Veintimilla and Guanujo, located at 2668 meters above sea level, the demography of the canine and feline population and its incidence on urban development was studied. The qualitative descriptive statistical model was applied in a total of 3503 pets. Percentages, means, frequency and graphs were determined. The objectives were: 1) Estimate the canine and feline population in the study area 2) Determine the demographic characteristics. 3) Establish the canine and feline relationship vs veterinary attention. The experimental variables and results were: Species 84% (canine) and 16%; (feline); Sex 57% male canine, 43% female canine and 58% male feline, 42% female feline; Breed 43% canine mestizo and 91% feline mestizos; Age 76% ˃ 6 month adult canine and 77% ˃ 6 month adult feline; Habitat 81% patio / canine and feline 66% patio / feline; Provenance 65% canine gift and 75% feline gift; Homemade diet 46% canine and 62% feline; Tenure 79% affection / canine and 89% affectivity / feline; Reason for consultation 39% canine / rabies immunization and 77% feline / rabies immunization; Medical frequency 45% rarely in canine and 53% never in feline. Finally, this research determined that the demographic study of the canine and feline population and its incidence on urban development in the city of Guaranda, were related by factors of emotional consideration to pets, socioeconomic strata, poor sanitary conditions which increases the public health risks, the awareness on the control of the reproductive life of their pets and the ignorance of responsibility in the possession of pets.